EASTERN RENAISSANCE AND ITS CULTURAL HERITAGE: THE VIEW OF FOREIGN RESEARCHERS (ResearchJet Journal of Analysis and Inventions, 2021)
Article covers the facts connected with life, scientific activities and socio-political views of the great thinkers and statesmen of Central Asia living in a wound of East Renaissance, more precisely in the 9-12th centuries and during board of temurid (the 14-15th centuries). Development of a world civilization prompts us that, such social factors as, emergence in the 9-12th centuries in Central Asia of the independent states, owing to prosperity of an Islamic civilization in our corner of the world appeared such scientists as Abu Nasr Farabi, Beruni, Ibn Sino, Nizamulmulk and during the second East Renaissance of such statesmen as Amir Temur, Alisher Navoiy. Now studying scientific heritage, socio-political activities and acquaintance youth charity of our above-stated ancestors is considered one of the main urgent objectives of the modern intellectuals.